ON SUPPRESSION OF CHAOTIC MOTIONS OF A PORTAL FRAME STRUCTURE UNDER NON-IDEAL LOADING USING A MAGNETO-RHEOLOGICAL DAMPER - Tusset, Angelo Marcelo; Piccirillo, Vinicius; Balthazar, Jose Manoel [UNESP]; Rebello da Fonseca Brasil, Reyolando Manoel Lopes (Polish Soc Theoretical & Applied Mechanics, 2015)
We consider chaotic motions of a portal frame structure under non-ideal loading. To suppress this chaotic behavior, a controlling scheme is implemented. The control strategy involves application of two control signals and nonlinear feedforward control to maintain a desired periodic orbit, and state feedback control to bring the system trajectory into the desired periodic orbit. Additionally, the control strategy includes an active magneto-rheological damper to actuate the system. The control force of the damper is a function of the voltage applied in the coil of the damper that is based on the force given by the controller.
Keywords: feedback control; feedforward control; MR damper